Peer interaction in class: exploring students’ self-regulation in relation to peer acceptance and rejection - Jakub Hladik; Karla Hrbackova; Anna Petr Safrankova (Cogent Education, 2024)
AbstractThe link between peer exposure and self-regulation is likely to vary as a function of the type and quality of peer interaction. In the presented research study, the relationship between self-regulation and peer acceptance/rejection has been explored. The Means-Ends Problem Solving technique was administered in 1625 cases of lower-secondary school students. A cluster analysis suggested three distinct profiles: Thriving, Balancing, and Struggling. Students in the Thriving profile demonstrated the highest level of self-regulation and the highest social acceptance in the peer group. Students with the Struggling profile showed the lowest level of self-regulation and the lowest social acceptance levels, but their perception of own inclusion in class was rather neutral. Profiling of students’ self-regulation skills enabled an enhanced understanding of the process of self-regulation in relation to peer interaction and offered new insights into the role of students’ attitudes (especially one’s perception of own inclusion in a peer group).